Concept of Transaction Costs in the Theory of O. E. Williamson - Tchipev, Plamen D. (Research Papers, 2021)
Launched briefly by Coase, the transaction costs concepts attracted attention and developed further in works of many scholars. The real importance, though, it acquired in the works of O. Williamson, who founded the economics of transaction costs (TRC) and the neo-institutionalism. Although, the original idea of Coase is subject of wide interpretations by the different authors, which raised the issue of continuity in its study. The present paper focuses on Williamson’s concept striving to reveal some specifics and differences in both interpretations.
Keywords: Transaction costs; Ronald Coase; Oliver Williamson